The Enigma of Lipofibromatous Hamartoma: A Deep Dive into a Rare Pathology (Global Journal of Medical Research, 2025)
lipofibromatous hamartoma (LFH) is a rare condition characterized by the infiltration of peripheral nerves by fibrous and adipose tissues. Patients typically present with gradually enlarging, non-tender lesions in the distribution of the affected nerve, most commonly the median nerve, which is involved in 66% to 80% of cases. Symptoms often include pain, sensory deficits, and motor dysfunction, with affected individuals reporting numbness and tingling along the volar aspect of the wrist and hand. Motor deficits tend to appear later in the course of the condition [1].